The costume making guide : creating armor & props for cosplay - Quindt, Svetlana (Cincinnati, Ohio : Impact, 2016)
"Packed with more than 30 step-by-step demonstrations that teach the skills you need to bring all your favorite characters to life no matter the genre, Kamui Cosplay deconstructs the work that goes into making a complete costume, from the first thought to the final photo. Tutorials cover design planning, fabricating body armor, 3D painting techniques and more. Best of all, you can adapt every lesson to use in all future fandom projects spanning video games, books, anime, movies and even your own original characters!"--Amazon.com.
What is cosplay? -- Why cosplay? -- Choosing a costume -- Finding good reference material -- Searching for inspiration -- What you need to get started -- Useful tools and materials -- Safety first! -- How to create a bracer : basic techniques from pattern making and shaping Worbla to priming, painting with acrylics, sealing and creating attachments -- How to create a breastplate : working with EVA foam, sealing with Plasti Dip and applying spray paint -- How to create a pauldron : shaping Worbla, applying and sanding spray filler and automotive spray paint -- How to create an axe : creating an EVA foam axe from a blueprint to the final prop -- How to create a sword : combining balsa wood and Worbla for prop creation -- A complete costume from start to finish : the entire construction process of a cosplay from the first thought to the final photo -- What's next : what to do once you've made your epic costume -- Costume inspiration gallery : more inspiring costumes by talented artists.
"Includes: expert instruction for rafting shiny armor and realistic looking props; how to choose a costume and find good reference art; a short shopping list of necessary materials and tools for beginning cosplayers; a beautiful photo gallery featuring inspiring images from other cosplayers; how to grow your workshop, take professional photos, participate in contests and join the cosplay community"--Page 4 of cover.
Includes index.
Keywords: Cosplay; Costume design; Armor